The Effect of Sexual Assertiveness Training on women's genital self-image: A Randomized Clinical Trial - Fatemeh Sayyadi; Nahid Golmakani; Amin Karim abadi (Mashhad University of Medical Sciences, 2021)
Background & aim: The genital self-image refers to women's attitudes, beliefs, and feelings about their genitalia and genital system that are involved in sexual intercourse. Sexual assertiveness is individuals' ability to meet their sexual needs. Considering the dearth of study on women's genital self-image, this study aimed to evaluate the effectiveness of a sexual assertiveness training program on women's genital self-image. Methods: This parallel randomized clinical trial was performed on 60 married women referred to Imam Reza Health Center in Mashhad during September and October 2016. A sample size of 30 subjects was assigned to intervention and control groups. The training classes including two 90 minutes sessions were held once a week for 2 consecutive weeks. The tools for data collection consisted of Hulbert sexual assertiveness and women's genital self-image questionnaires. A pretest was completed in two groups at the beginning of the study and a post-test was done for both groups one week after training the intervention group. To analyze data student t-test, paired t-test, Mann-Whitney, Wilcoxon, Chi-square and one-way analysis of variance were used. Results: The score of genital self-image was the same in two groups before carrying out the intervention (z= -1.762, p= 0.780). However, following the implementation of training program the two groups showed significant differences and the score of genital self-image  was higher in intervention group (z = - 4.077, p ˂ 0.001).   Conclusion: Sexual assertiveness training can improve women's genital self-image. So it is recommended to tailor training programs to enhance women's genital self-image, particularly, in women with sexual dysfunction in order to improve their sexual health.